Failure Analysis of Corrosion-Induced Perforation in B10 Copper-Nickel Alloy Pipelines - SONG Shuai, QIN Limin, SUN Yujiang, ZHANG Shangfeng, YANG Wenming, HE Yueyang, XU Zhigang (Cailiao Baohu)
The B10 copper-nickel alloy pipeline used for seawater transportation on a certain platform was found to have corrosion perforation at the weld joint between the elbow and the flange during a shutdown inspection.In this study， the failure mechanism of corrosion perforation was analyzed using macroscopic morphology observation，scanning electron microscopy (SEM)，energy-dispersive spectroscopy (EDS)，X-ray diffraction (XRD) and metallographic examination.Results showed that “sugar cube”-like intergranular corrosion morphologies were commonly observed at the bottom of corrosion pits on the flange， in erosion-wear areas， corrosion grooves， perforated regions and at the bottom of corrosion pits on the elbow.Locally， a “stepped” exfoliation morphology was observed， where grains were progressively stripped layer by layer.The preferentially corroded grain boundaries formed a circuit， and the surrounded grains were selectively denickelized and dissolved， resulting in grain spalling.The reduced hardness and coarse columnar grain structure of the flange further decreased the material’s corrosion resistance.The corrosion perforation of the copper-nickel alloy pipeline occurred in the erosion-sensitive zones and the weld heat-affected zones with the poorest corrosion resistance.This failure was the result of the synergistic effects of erosion wear， intergranular corrosion and selective dealloying.Enhanced corrosion monitoring is recommended for similar locations in service pipelines.